Demonic mnemonics 800 spelling tricks for 800 tricky words - Suid, Murray I. (Pitman Learning, 1981)
Presents 800 of the most commonly misspelled words in the English language and links each word to a memorable spelling trick intended to make the proper spelling unforgettable.